Newborn screening programmes in Europe; arguments and efforts regarding harmonization: Part 1 - From blood spot to screening result - Loeber, J. Gerard; Burgard, Peter; Rupp, Kathrin; Hoffmann, Georg F. (Journal of inherited metabolic disease, 2012)
In many European countries neonatal screening has been introduced over the last 50 years as an important public health programme. Depending on health care structure, available funds, local politics, input from professional groups, parent groups, and the general public this introduction has led to different approaches in the way the screening programmes have been set up, financed and governed. To get some insight about the current situation, in 2009 the European Union, via its EAHC agency, put out a call for a tender that was acquired by our project group. An online survey was compiled in which the whole screening programme was covered by a questionnaire. This survey covered the EU member states, (potential) candidate member states and EFTA countries, in total 40 countries. Results showed little consensus concerning 1. information of parents including informed consent; 2. which conditions are screened for, ranging from 1 to around 30 conditions; 3. sampling time post partum; 4. screening methodology including cut-offs values even between screening laboratories within countries.; 5. storage of residual specimens, varying from 3 months to 1000 years. In addition, confirmatory diagnostics and follow-up also show large discrepancies (Burgard et al. http://www.iss.it/cnmr/prog/cont.php?id=1621&lang=1&tipo=64 2011). In addition to the current practices report an expert opinion document has been produced with recommendations to the EU Commission for future improvements, e.g. in parallel to the way the USA has harmonized its practices based on recommendations by the American College of Medical Genetics (Watson et al., Pediatrics 117: S296-S307, 2006).
Gesehen am 26.10.2018
Presented at the Annual Symposium of the SSIEM, Geneva, Switzerland, August 30 - September 2, 2011